2015
DOI: 10.1093/intimm/dxv002
|View full text |Cite
|
Sign up to set email alerts
|

Association between sHLA-G and HLA-G 14-bp deletion/insertion polymorphism in Crohn’s disease

Abstract: The aim of this study was to evaluate the association between the HLA-G 14-bp deletion/insertion (Del/Ins) polymorphism and soluble (s) HLA-G production in patients with Crohn's disease (CD). We analyzed also the sHLA-G molecules by ELISA and western blot in plasma samples. Among unselected patients, the 14-bp Del/Ins polymorphism was not significantly associated with increased CD risk neither for alleles (P = 0.371) nor for genotypes (P = 0.625). However, a significant association was reported between the 14-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
4
19
0
1
Order By: Relevance
“…Notwithstanding that, this meta-analysis revealed inconsistencies between some association studies that have already been published. This statement is based on the following results: i) when we observed data from many conditions (Cervical cancer, Hepatocellular carcinoma, Multiple sclerosis, Rheumatoid arthritis, HIV vertical transmission, Human papillomavirus infection, Heart transplantation, Kidney transplantation, Preeclampsia (mothers), Implantation failure, Miscarriage, e.g), we could verify that some studies found the 14-bp insertion associated with susceptibility to disease development [108,112,[117][118][119]138,140], whereas, others revealed the 14-bp deletion as the allele associated with susceptibility [47,53,79,82,91], and sometimes none was associated [48,49,80,98,101,105,147]; ii) when the disorders were grouped according to conditions exhibiting a hypothetical high (1) or low (2) HLA-G expression, no associations between the 14-bp alleles were All possible associations between 14-bp polymorphism and the clinical situations/diseases were measured by calculating a pooled Odds Ratio (OR) and 95% confidence intervals (CI) for fixed and/or random effect models. The p values resulting from the Q test, τ2 values and of the I2 value were used to measure betweenstudies heterogeneity.…”
Section: Discussionmentioning
confidence: 73%
“…Notwithstanding that, this meta-analysis revealed inconsistencies between some association studies that have already been published. This statement is based on the following results: i) when we observed data from many conditions (Cervical cancer, Hepatocellular carcinoma, Multiple sclerosis, Rheumatoid arthritis, HIV vertical transmission, Human papillomavirus infection, Heart transplantation, Kidney transplantation, Preeclampsia (mothers), Implantation failure, Miscarriage, e.g), we could verify that some studies found the 14-bp insertion associated with susceptibility to disease development [108,112,[117][118][119]138,140], whereas, others revealed the 14-bp deletion as the allele associated with susceptibility [47,53,79,82,91], and sometimes none was associated [48,49,80,98,101,105,147]; ii) when the disorders were grouped according to conditions exhibiting a hypothetical high (1) or low (2) HLA-G expression, no associations between the 14-bp alleles were All possible associations between 14-bp polymorphism and the clinical situations/diseases were measured by calculating a pooled Odds Ratio (OR) and 95% confidence intervals (CI) for fixed and/or random effect models. The p values resulting from the Q test, τ2 values and of the I2 value were used to measure betweenstudies heterogeneity.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, they observed higher sHLA-G levels in CD patients than in controls, and they found that patients with 14 bp del/del and 14 bp del/ins genotypes are the high HLA-G producers. Dimers of sHLA-G were found in advanced disease stage, thus suggesting a role for sHLA-G as a prognostic marker for progressive disease in CD patients [ 65 ]. Dimers of sHLA-G have been also analyzed by Fainardi et al in MS.…”
Section: Hla-g In Autoimmune/inflammatory Diseasesmentioning
confidence: 99%
“…Studies have shown that adipose tissue secretes various inflammation-related cytokines, such as leptin and IL-6, which can induce chronic low-grade inflammation in obese individuals, with a concomitant stimulation of sHLA-G production, which has anti-inflammatory activities [21,22]. This mechanism is possibly due to compensate the chronic pro-inflammatory state of obesity.…”
Section: Discussionmentioning
confidence: 99%